Boehmeria nivea var. strigosa(Urticaceae), a new variety from Southwest China - ZHAO Ying1,4, Richard I. MILNE5, LI Zhipeng1,2,4, Amos KIPKOECH1,3, WU Zengyuan1* (Guangxi Zhiwu)
Boehmeria nivea var. strigosa Zeng Y. Wu & Y. Zhao, a new variety of B. nivea(Urticaceae)from Southwest China, is here described based on evidence from morphology and molecular phylogeny. This new variety is mainly characterized by its green abaxial leaf blade, partly connate stipules, and densely patent strigose hairs on stems and potioles. The phylogenetic analysis based on rbcL, nrDNA and rbcL+nrDNA datasets, revealed that all individuals of B. nivea var. strigosa formed a monophyletic group. The conservation status of B. nivea var. strigosa is assessed as “Near Threatened”(NT)according to IUCN evaluation criteria. The discovery of this new variety is not only crucial for the taxonomy of ramie, but also provides reference for the exploration and utilization of ramie.